Conciliación entre el Universo, el ser humano y la educación universitaria - Ileana Castillo-Cedeño (Revista Electrónica Educare)
This reflection emerges from the experience I have lived as a student and as an academic university professor with the hope that superior education can have the opportunity and potential to renew and vitalize the formal educational processes, from the point of view the paradigm of complexity wich assumes the close relation between the human being and the Universe.